Planting Character Education at TK Aba 25 Wage During a Pandemic - Sayyidah Mahbuubah (International Consortium of Education and Culture Research Studies, 2021)
The formation of student character is something very important but not easy to do, because it needs to be done in a long process and lasts a lifetime. Moreover, the character is not directly owned by the child since he was born, but the character is obtained through various kinds of experiences in his life. Character education begins to be instilled in students from an early age which is very important because at this time there is a golden age in this golden age, the opportunity is quite large for the formation and development of one's personality. The purpose of this article is to form a character in children to make children more focused in the future, the goal is that later generations of the nation can understand, appreciate, and be able to practice the values of character education. Early childhood education is very important to be carried out as a basic material for the formation of a human personality as a whole, namely for the formation of character, noble character, intelligent, cheerful, skilled, and devoted to God Almighty. Early childhood education can be started from home or in family education. Character education is very important to build a civilized nation, character education should have been instilled since early childhood so that they are very appropriate if they are made beginners for character building because children are at the golden age.